Essays in Normative Economics - Bergson, Abram (Cambridge : Belknap Press of Harvard University Press, 1966)
This book is a much needed addition to the factual findings on the Soviet Union. It is an enormous march forward in real economic knowledge about the Soviet Union.
Bibliographical footnotes.
osa;01/11/17
Loans
Keywords: Welfare economics; Marxian economics